An analysis of the visual portrayal of women in junior secondary Malawian school history textbooks (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
Visual images are important in textbooks because they are a vital part of the symbiotic relationship with the written text. Most importantly, visual images are essential in history textbooks because they render human experiences less abstract. This article analyses the visual images of women contained in three junior secondary school history textbooks used in Malawi. The purpose being to explore how women are portrayed visually and why they are portrayed the way they are. The article is based on empirical research and employed feminist theory which is premised on the oppression and subordination of women in society. The visual images were analysed quantitatively through visual content analysis and qualitatively using visual semiotic analysis. We argue in this article that women are generally oppressed, under-represented and subordinated in their portrayal in the visual images in the textbooks analysed. As textbooks are authoritative in nature this kind of portrayal can send a certain message about women as historical characters to textbook users. We furthermore argue that our research findings in an African context speak to similar findings in other parts of the world and can for the most part be attributed to similar reasons - the powerful influences of patriarchy on both history and history textbooks.